A Hypothesis on Suspension Feeding in Early Chelicerates (Offacolidae) - Lorenzo Lustri; Luis Collantes; Cristiana J. P. Esteves; Robert J. O’Flynn; Farid Saleh; Yu Liu (Diversity, 2025)
The Cambrian–Ordovician Plankton Revolution played a crucial role in the Great Ordovician Biodiversification Event (GOBE) or Ordovician Radiation, as a driver of diversification. The emergence of new planktonic species enhanced primary productivity and improved nutrient cycling, fueling diversification across trophic levels. In this context, established plankton consumers like sponges and cnidarians thrived, and animals like euarthropods also radiated in response to these environmental conditions. Here, we hypothesize that Offacolidae, a small group of early chelicerates (the group including sea spiders, spiders, mites, and horseshoe crabs) known from the early Ordovician to the end of the Silurian, were suspension feeders that diversified within this changing ecosystem. Extant chelicerates are primarily predators or parasites, with no known cases of suspension feeding, which is also the case in extinct members. However, anatomical and environmental evidence suggest that Offacolidae may have adopted this feeding strategy. We examine the environmental conditions in which Offacolidae fossils were found, considering both biotic and abiotic factors such as paleolatitude, bathymetry, and the associated plankton community. We also assess the possible biomechanics of their unique appendages to determine their suitability for suspension feeding. Finally, comparisons with extant arthropods, such as the suspension-feeding crustaceans Limnomysis benedeni, Atya gabonensis, Subeucalanus pileatus, and the genus Emerita, provide insights into possible evolutionary analogies in their morphology, which may have served the same function. If confirmed, this hypothesis would make Offacolidae a unique case within chelicerates, illustrating how exceptional early Ordovician conditions fostered novel ecological adaptations and highlighting an interesting case of analogy between different lineages of euarthropods.